KAJIAN DESAIN KARAKTER PERSONA 4 BERDASARKAN PENDEKATAN ARCHETYPE DAN MANGA MATRIX - Ika Resmika Andelina (Universitas Mercu Buana, 2020)
Games are often used as an entertainment medium that occupies a place in the hearts of consumers. One type of game that still has a high interest in console games. Persona 4 is a Playstation game that was released on July 10, 2008, and won the Game of the Year title from many game criticism and media review games. Persona 4 was praised for its unique visual style, interesting and powerful stories, and the bold adoption of social themes and gender sexuality. The visual aspect of Persona that will be analyzed in this research is related to the creation and design of characters in intellectual property. This research will be examined in terms of overall character design, using Carl Jung's Archetype approach to dissect personality characterization, then its relation to visual using Hiroyoshi Tsukamoto's Manga Matrix approach and then deepened by using intertextual theory to dissect conceptually, as well as what aspects influence the character's creation. So it is hoped that the results of this study can be a reference material for developing character design created in the world of learning and also industry, especially in the gaming industry, to create fantasy characters that have an appeal in attracting players.